Diversity of Milks Other Than Cow, Sheep, Goat and Buffalo: In Terms of Nutrition and Technological Use - Marlon Numpaque; Tuba Şanlı; Elif Ayse Anli (Turkish Journal of Agriculture: Food Science and Technology)
The first introduction of human being with milk begins with human milk during infancy, continues with very commonly with cow’s milk and may be with other milk types during lifetime. Cow breeding and utilizing its milk in nutrition is widespread in the world. There are particular species common to their area such as donkey, camel, mare, yak and llama have an important share in milk production in the world. Donkey milk has higher serum protein and lower casein content being similar to human milk so regarded as a good and safer alternative for infants suffering from cow’s milk protein allergy. Mare milk is used as a therapeutic agent for the treatment of some metabolic and allergic illnesses. It is generally consumed as fermented product. Llama milk contains higher amounts of calcium and phosphorus than cow's milk. Camel milk has high vitamin and mineral content and has claimed to have medicinal proteins. Its casein micelle size is larger naturally and it has lower amount of κ-casein these cause difficulties in cheese making and affect curd quality. Reindeer milk is an energy dense food with its high fat and high protein content when compared to cow’s milk. Its high protein content could make it suitable for protein supplementation. Its low lactose content makes its consumption possible by lactose intolerance patients. Yak is richer in almost all main nutritional components when compared with cow’s milk. It can be used in cheese, butter making and dried milk products. The objective of this review was to represent the composition of different animal species’ milks; other than cow, buffalo, sheep and goat, their importance in nutrition and technological use.